2013
DOI: 10.1111/pedi.12081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impaired fasting glucose and analysis of related factors in Taiwanese adolescents

Abstract: The prevalence of IFG in Taiwanese adolescents is a public health issue that should not be ignored. The prevalence may be reduced by adjusting lifestyles. Healthy family environments should be encouraged and appropriate healthy lifestyle counseling plans offered specifically to male adolescents with overweight, obesity, and cardio-metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…In contrast, among obese/overweight Emirati children and adolescents (aged 11‐17 years), prediabetes prevalence was estimated to be 21.9% according to the HbA1c ADA criteria . As for international studies, prediabetes prevalence among the general population of children and adolescents in the United States (HbA1c ADA : 17.8%) and Taiwan (IFG ADA : 22.0%) were less than our estimated prevalence. The discrepancies between studies can be, in part, explained by the different applied screening tools and diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, among obese/overweight Emirati children and adolescents (aged 11‐17 years), prediabetes prevalence was estimated to be 21.9% according to the HbA1c ADA criteria . As for international studies, prediabetes prevalence among the general population of children and adolescents in the United States (HbA1c ADA : 17.8%) and Taiwan (IFG ADA : 22.0%) were less than our estimated prevalence. The discrepancies between studies can be, in part, explained by the different applied screening tools and diagnostic criteria.…”
Section: Discussioncontrasting
confidence: 81%
“…These findings support the need for rigorous metabolic screening and implementation of lifestyle changes at an early stage, given impaired fasting glucose being an important biomarker associated with obesity and future metabolic syndrome. 4,5 More research is required to evaluate whether these earlier lifestyle modifications or preemptive administration of hypoglycemic agents could prevent the development of TH or even worse diabetic complications in patients at high risk.…”
Section: Comment On: Glucose Levels Before the Onset Of Asparaginase mentioning
confidence: 99%
“…Several cross‐sectional studies among adolescents have shown a wide range in the prevalence of IFG, from 3.5% among Chinese adolescents to 40.5% among Americans, depending on the population studied. However, limited studies have investigated the temporal changes of prediabetes in this age group .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 According to the third study of the school-based surveillance system entitled CASPIAN III (2009)(2010), in a representative sample of the Iranian adolescents, the prevalence of fasting plasma glucose (FPG) ≥ 100 mg/dL among boys and girls was 12.2% and 18.5%, respectively, a prevalence significantly higher in girls. 8 Several cross-sectional studies among adolescents have shown a wide range in the prevalence of IFG, [9][10][11] from 3.5% among Chinese adolescents 12 to 40.5% among Americans, 13 depending on the population studied. However, limited studies have investigated the temporal changes of prediabetes in this age group.…”
Section: Introductionmentioning
confidence: 99%